Mutual interactions of oscillating quartz tuning forks in superfluid 4He: Квантованные вихри и турбулентность - Sheshin, G.; Gritsenko, I.; Schmoranzer, D.; Skrbek, L. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
The quartz tuning fork has recently become a popular experimental tool for investigations of both classical and quantum turbulence in cryogenic helium. Its increased use in low-temperature experiments and a number of puzzling results obtained in the past have led to many questions concerning the interaction of multiple tuning forks or the interaction of tuning forks with other oscillators. We report measurements performed in He II at low temperatures around 360 mK, on the mutual interaction of tuning forks placed in the same volume of fluid, and examine the responsible mechanisms in an effort to discriminate between acoustic coupling and interaction via quantized vortices. To this end, the interaction of two tuning forks is investigated by analyzing their recorded resonance curves, looking for any nonelectrical crosstalk. Further, the force-velocity characteristics of a detector tuning fork are measured for different operating velocities of a generator tuning fork. As a complementary measurement, the intensity of sound waves is recorded using a set of miniature receivers. We confirm the current knowledge on acoustic emission by tuning forks in He II and verify properties of their radiation patterns. We conclude that in our experiment the interaction is almost entirely mediated by sound waves.